Pakistan - Strengthening the Insolvency Regime : Non-Lending Technical Assistance Final Report - World Bank (Washington, DC, 2013)
The importance of a modern, binding and effective insolvency regime is undeniable. Nearly 90 countries around the world have reformed their bankruptcy codes since Second World War, and over half of them have done so during the last decade. One of the key aspects in the reform process is the delicate balance addressed by a modern insolvency system which encourages the organization of viable firms and liquidates unviable firms. The financial and macroeconomic crises, as recently experienced in Pakistan, provide an opportunity for bankruptcy reform, as the potential employment impact often places the issue of insolvent companies high on the policy agenda. The three fundamental goals of any insolvency law are: 1) transparency, including a system for publicizing and indexing judgments, an accessible method for registering securing interest and an effective notice of insolvency proceedings, 2) predictability - in terms of being fair, simple and clear, which if not achieved ends up costing more as financial institutions compensate the uncertainty with additional credit costs; and 3) efficiency, which conceptually is clear but empirically is difficult to measure.